PENGARUH MOTIVASI DAN KOMUNIKASI TERHADAP KINERJA KARYAWAN DI PT KRISTAL KOMPUTERINDO PERKASA - Lauw, Hernawati; Purba, Tiurniari (LPPM Universitas Putera Batam, 2022)
Every company will always attempt to pursue the goals that they determine. The goals can be achieved if the company does not merely count on the superiority of technology, operating funds, available facilities, and infrastructure, bute they should also pay attention to numerous resource aspects that the company owns. This studies was aimed at testing and analyzed the Problems of Motivation and Communication on Employee Performance at PT Kristal Computerindo Perkasa. The technique utilized in this study encompassed a saturated sample or census comprising 104 respondents in total. The instrument utilized to measure the data encompassed 5 point likert scale.The analytical method utilized was multiple linear regression assisted by SPSS 25. Grounded on the results, it was indicated that Motivation and Communication positively and significantly affect employee performance from t calculate > t table and its significant value accounted for <0.05; they simultaneously give positive and significant effects on employee performance.